Comparison on Supplementation with Waste of Soybean “Tao Hou” on Growth Performance in Local “Yellow” Cattle Fed Ensiled Cassava Roots as Basal Diet - Inthapanya, Sangkhom; Phongphanith, Sengsouly; Vannasouk, Sinthanou (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
This study undertook an assessment of the potential benefits in term of supplementing the soybean waste on growth performance from local “Yellow” cattle fed a basal diet of ensiled cassava roots (ie: yeast, urea, di-ammonium phosphate and Napier grass) and straw. There were eight local “Yellow” cattle with initial weight of 82kg. The 02 treatments in a completely randomized design were: NWSS (No waste of soybean supplement) and WSS (Waste of soybean supplement) at a predicted level of 10% of diet DM (ECR). Ensiled cassava roots (ECR) were fed ad-libitum and rice straw was fed at 1% of live weight (DM basis). The animals were weighed at the beginning of the study and then every fifteen days until the study was completed for measurement the live weight change. Feed offer and residue samples were collected from the animals in the morning before feeding, and every 15 days during the study for determine the feed intake. The results showed that total feed intake, the average daily live weight gain (ADG), and feed conversion ratio (FCR) of cattle receiving ensiled cassava roots, straw and supplemented with waste of soybean were significantly higher (P<0.05) than for animals receiving the ensiled cassava roots, straw and no supplemented with waste of soybean. The total feed intake was higher for cattle receiving supplemented with waste of soybean were 3085gDM per day when compared with no supplement 2782g DM per day (There was increased feed intake 9.82% with supplementing treatment). The average daily live weight gain for cattle receiving supplements was 323g per day higher than that treatment receiving no supplement. This animal receiving supplement was trend in an increasing the average daily live weight gain at 24.8% when compared with no supplements, there were only ensiled cassava roots and straw as basal diet. The feed conversion was better for animals receiving supplemented at 9.22 and 12.5 when compared with no supplement respectively. Supplementing on waste of soybean by using ad-libitum of ensiled cassava roots (Yeast, urea, di-ammonium phosphate and Napier grass) and straw as basal diets provides the joint potential of being a protein supplement for ruminants especially increasing feed intake and growth performance of local “Yellow” cattle and it’s readily accessible for smallholder producers through intensive cattle fattening